Journal publication productivity of women scientists at Bhabha Atomic Research Centre, India. (1st January 2014) - Upadhye, Rekha P.; Girap, Priya Vijay; Tewari, Shalini; Ashok, Tara; Bhanumurthy, K.; Sinha, Ratan Kumar
Contributions in academia especially science and technology are important indicators to gauge the progress and participation of women. The objective of the study was to evaluate the contribution of Bhabha Atomic Research Centre (BARC), India, women scientists. This study analyses 5290 publications in journals for the period 2006–2010. Out these, 1455 (27.50%) publications had at least one author as a BARC woman scientist. Average contributing women authors were 36% out of 5762 both BARC men and women contributing authors. Highest numbers of publications were from Physical Sciences (28.52%), followed by Chemical Sciences (27.7%), Biological Sciences (19.04%), Materials Science (13.06%), Environmental Sciences (7.08%) and Engineering & Technology (4.6%). Collaborative analysis indicated 69.67% intra-BARC, 17.68% national and 12.65% international collaboration. Based on critical analysis it was found that there were 634 women scientists, which is 16% of the total number of scientists and they contribute about 36% of technical journal publications.